2015
DOI: 10.1097/meg.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Chronic severe constipation

Abstract: Chronic constipation is a considerable problem because it significantly affects the quality of a patient's life. Constipation can be diagnosed at every age and is more frequent in women and among the elderly. In epidemiological studies, its incidence is estimated at 2-27% in the general population. Chronic constipation may be primary or secondary. However, primary constipation (functional or idiopathic) can be classified into normal transit constipation, slow transit constipation, and pelvic outlet obstruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…Despite previous studies that reported OIC occurring more frequently in women and patients aged ≥ 50 years, we did not observe correlations between sex or age and incidence of OIC. Rather, these earlier findings may have been the result of higher rates of chronic constipation in these patient subgroups and may not have been specific to OIC . The current study excluded patients with chronic constipation, thereby eliminating potential confounding effects of sex‐ or age‐related risk associated with chronic constipation.…”
Section: Discussionmentioning
confidence: 89%
“…Despite previous studies that reported OIC occurring more frequently in women and patients aged ≥ 50 years, we did not observe correlations between sex or age and incidence of OIC. Rather, these earlier findings may have been the result of higher rates of chronic constipation in these patient subgroups and may not have been specific to OIC . The current study excluded patients with chronic constipation, thereby eliminating potential confounding effects of sex‐ or age‐related risk associated with chronic constipation.…”
Section: Discussionmentioning
confidence: 89%
“…The complete absence or a significant reduction in the number of ICCs in colon specimens resected from patients with STC has been reporeted in comparison with normal controls ( 6 ). In addition, a number of other pathophysiological abnormalities, including the degeneration of the myenteric plexus ganglia, the aberrant expression of smoothelin protein, and abnormalities of the enteric neurotransmitters may be associated with constipation ( 7 , 8 ). However, the mechanisms through which these numerous abnormalities contribute to the pathogenesis of constipation remain to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic mechanisms for STC have been discussed. Several studies have suggested that propagating motor contractions are deficient in STC [12][13][14][15] and medical treatment usually aims at increasing intestinal secretion or stimulating and restoring motor function. Inflammatory and degenerative changes in myenteric ganglia as well as altered levels of enteric neurotransmitters have been discussed in the pathophysiology of STC [14].…”
Section: Discussionmentioning
confidence: 99%